2018
DOI: 10.1002/ijc.31414
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐mediated antitumor effect of a transplanted lymph node

Abstract: Lymph node (LN) transplantation is a recognized method for reconstruction of the lymphatic system and is used in the clinical setting to treat lymphedema. However, it is unclear whether transplanted LNs contribute to immune surveillance. In our study, we investigated whether a single transplanted non-vascularized LN, defined as a tumor-draining transplanted lymph node (TDTLN), could exert an immune-mediated antitumor effect. LN and lung metastases and primary tumor enlargement were evaluated in mice that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Moreover, a PLN could be regarded as the sentinel lymph node, which is the primary site where the immune system encounters tumor antigens in a mouse model inoculated with B16F10 melanoma cells, syngeneic and transplantable to the C57BL/6 mouse strain, into the hindlimb footpad (Maeda, Hayashi, et al, ). We believe that our model will be useful for further investigating the physiologic and immunologic functions of the transferred vascularized lymph nodes as well as the biological significance of these functions in terms of tumor immunity (Maeda, Hayashi, et al, ; Oashi et al, ; Rabson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a PLN could be regarded as the sentinel lymph node, which is the primary site where the immune system encounters tumor antigens in a mouse model inoculated with B16F10 melanoma cells, syngeneic and transplantable to the C57BL/6 mouse strain, into the hindlimb footpad (Maeda, Hayashi, et al, ). We believe that our model will be useful for further investigating the physiologic and immunologic functions of the transferred vascularized lymph nodes as well as the biological significance of these functions in terms of tumor immunity (Maeda, Hayashi, et al, ; Oashi et al, ; Rabson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A mouse model would be advantageous to investigate the immune function mechanism with numerous antibodies. We recently reported, using a mouse model inoculated with B16F10 melanoma cells, the immune‐mediated antitumor effect of nonvascularized lymph node autotransplantation (Maeda et al, ). However, autotransplantation of lymph nodes is rarely performed in clinical situations because of lymphedema after lymphatic injury during cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…and lymphocytes) can regulate the balance of the host inflammatory and immune status, which are associated with prognostic value in multiple tumor types[34][35][36][37][38]. Several mechanisms can potentially explain why peripheral blood parameters statistically affect OS or PFS in cancer patients.…”
mentioning
confidence: 99%
“…In contrast, Sasaki et al found that HEVs appeared 10 days after nonvascularized mesenteric LNT with fragmentation, and the regeneration of transplanted LN fragments was structurally complete with normal HEVs on day 28 in a rat autograft model . Using a murine model inoculated with B16F10 melanoma cells, we recently demonstrated that the lumens of HEVs in a nonvascularized autotransplanted PLN were not dilated when compared with those in an intact PLN 6 weeks after surgery in the premetastatic phase …”
Section: Discussionmentioning
confidence: 67%
“…Using a murine model inoculated with B16F10 melanoma cells, we recently demonstrated the immune‐mediated antitumor effect of nonvascularized LN autotransplantation through activation of T‐cells, showing the expansion of lymphocytes and a change in the lymphocyte population . In that study, the function of the transplanted LN was affected by the change in HEVs brought about by decreased vascularity, so maintaining vascularization may also be important for regeneration of HEVs to maintain the immune functions of the LN. Accordingly, we evaluated the feasibility of pedicled vascularized LNT in a murine model with a postoperative assessment of lymphatic flow using indocyanine green lymphography …”
Section: Introductionmentioning
confidence: 86%